The oral health and treatment needs of schoolchildren in Trinidad and Tobago: findings of a national survey - R. NAIDU, I. PREVATT, & D. SIMEON (Paediatric Dentistry, 2006)
To describe the oral health and treatment need of choolchildren in Trinidad and Tobago.